Biochar and compost enhance soil quality and growth of roselle (Hibiscus sabdariffa L.) under saline conditions - Di Liu; Zheli Ding; Esmat F. Ali; Ahmed M. S. Kheir; Mamdouh A. Eissa; Omer H. M. Ibrahim (Scientific Reports, 2021)
Abstract Soil amendments may increase the slate tolerance of plants consequently; it may increase the opportunity of using saline water in agricultural production. In the present pot trial, the effects of biochar (BIC) and compost (COM) on roselle (Hibiscus sabdariffa L.) irrigated with saline water (EC = 7.50 dS m−1) was studied. Roselle plants were amended with biochar (BIC1 and BIC2) or compost (COM1 and COM2) at rates of 1 and 2% (w/w), as well as by a mixture of the two amendments (BIC1+). The experiment included a control soil without any amendments. Biochar and compost significantly enhanced the soil quality and nutrients availability under saline irrigation. Compost and biochar improved the degree of soil aggregation, total soil porosity and soil microbial biomass. BIC1 + COM1 increased the soil microbial biomass carbon and nitrogen over the individual application of each amendments and control soil. BIC1 + COM1 increased the activity of dehydrogenase and phosphatase enzymes. Growth of roselle plants including: plant height, shoot fresh and dry weight, and chlorophyll were significantly responded to the added amendments. The maximum sepal’s yield was achieved from the combined application of compost and biochar. All the investigated treatments caused remarkable increases in the total flavonol and anthocyanin. BIC1 + COM1 increased the total anthocyanin and flavonol by 29 and 17% above the control. Despite the notable improvement in soil and roselle quality as a result of the single addition of compost or biochar, there is a clear superiority due to mixing the two amendments. It can be concluded that mixing of biochar and compost is recommended for roselle plants irrigated with saline water.